Peripheral monuments: book review of Thinking Design: Blueprint for an Architecture of Typology by Andreas Lechner - McEwan, Cameron (Journal of Architecture and Urbanism, 2022)
In Thinking Design: Blueprint for an Architecture of Typology Andreas Lechner reassesses the question of architectural typology in relation to design research, practice, and theory. The book is organised into three extended chapters, entitled: Tectonics, Type, and Topos. In dialogue with the text are drawings of 144 important buildings from ancient times to the twenty-first century, focused on civic typologies. Each of those typologies incorporates a suite of 12 examples drawn in neat line drawings at a consistent scale. An enclosed booklet features design theses extracts by twelve students of TU Graz that illustrate Lechner’s approach to teaching and design. I reflect on each chapter and argue that Thinking Design offers an original theoretical reflection on the status of the urban periphery and opens compelling questions about architecture and architectural design research as a practice of critical inquiry.